118 Case series: subacute combined degeneration of the spinal cord in vitamin B12-replete recreational nitrous oxide abusers. (29th July 2019) - Blair, Chris; Tremonti, Chris; Edwards, Leon; Haber, Paul; Halmagyi, Michael
Abstract : Introduction: Within a few years of its discovery in late 18 th century, nitrous oxide was being used recreationally for its pleasurable effects. It remains in widespread use as an inhaled stimulant today, and can be legally acquired in bulk quantities with relative ease. In the body prolonged exposure to nitrous oxide leads to the oxidization of vitamin B12, rendering it unusable in key enzymatic reactions necessary for myelin synthesis. Over time this qualitative deficiency leads to a central demyelination syndrome that characteristically develops despite normal serum vitamin B12 levels and, with continued exposure to nitrous oxide, resists treatment with vitamin B12 supplementation. Method: Nitrous oxide abusers presenting with a central demyelination syndrome were enrolled in this case series. Serum levels of vitamin B12, active B12, folate and homocysteine were measured. Nitrous oxide exposure was discontinued, and all patients were treated in accordance with evidence-based guidelines. Results: Eight patients presented with predominantly moderate-to-severe clinical deficits. The majority were vitamin B12 replete. In most cases individuals had actively engaged in prolonged vitamin B12 supplementation in an attempt to circumvent the harmful pathophysiology, of which they were loosely aware. Following treatment and rehabilitation several patients were discharged into full-time care, and most had significant residual disability at follow-up. Conclusions: This case series not only illustrates the tragic consequences of abuse of this widely available and legally procured stimulant, but also highlights the futility of pursuing a nominally 'protective' strategy of vitamin B12 supplementation in the context of continued nitrous oxide exposure.